INNOVATION STRATEGIES: THE PATTERNS ACROSS COUNTRIES, INDUSTRIES AND FIRM COMPETITIVENESS - Stankevice, Inga (European Scientific Journal, ESJ, 2014)
The paper is aimed at the identification of firm-level innovation strategies and their competitiveness across sectors and countries. The types of innovation strategies are identified based on exploratory techniques that are applied to CIS6 microdata. The data includes 60 innovation variables from 16 European countries, 12 core and 19 additional industrial sectors. The total sample size equals 127,674 firms. The dispersion of the emerged innovation strategies across the sample countries and sectors is presented as well. Firm competitiveness pattern typical of the innovation strategies is also assessed. The suitability of the established innovation strategies for other than CIS6 economies is defined, thus allowing for the generalization of the results at the global level. For this purpose, the data of the Institutional Profiles Database III from 123 countries are employed. Both the identification of the competitiveness pattern along the emerged innovation strategies and the possibility to generalize the results at the global level are novel for this strand of work. From the practical perspective, the findings enable firms to better evaluate the appropriateness of the relevant economies to their innovation strategies. Thus, for instance, institutional contexts of some economies can be considered to be suitable for the most competitive innovation strategies, but firms in these economies do not fully utilize this potential. Hence, the findings could be used by them as the guidelines for further innovation development.